Stability Analysis of Efficient Portfolios in a Discrete Variant of Multicriteria Investment Problem with Savage's Risk Criteria - Vladimir Emelichev; Yury Nikulin; Vladimir Korotkov (Computer Science Journal of Moldova, 2017)
We consider a multicriteria discrete variant of investment portfolio optimization problem with Savage's risk criteria. Three combinations of norms in problem parameter spaces are considered. In each combination, one of the three spaces is endowed with Hölder's norm, and the other two spaces are endowed with Chebyshev's norm. The lower and upper attainable bounds on the stability radius of one Pareto optimal portfolio are obtained.